Coronavirus from Slavoj Žižek's perspective: From Capitalism to Communism (Raparin Journal of Humanities (RJH), 2023)
The world system has followed capitalism. According to Slavoj Žižek, capitalism is facing many crises. One of the crises created by this system is the coronavirus pandemic. Since capitalism thinks only in terms of profit and the market, it cannot overcome this pandemic with its own rules. Moreover, the main culprit is the political model of capitalism, neoliberalism, as it becomes increasingly barbaric through privatisation, corporations, media and social media. Meanwhile, the coronavirus has instilled fear in people's hearts and expanded the power of the state over citizens. Žižek argues that all these help to sprout socialism and pave the way for a new form of communism. This stems from the fact that capitalist mechanisms and tools cannot prevent a crisis such as the coronavirus. Instead, states, organisations and individuals must resort to communism. This communism embodies more cooperation and coordination, because in times of crisis, neither the state alone and without the cooperation of members of society can overcome the crisis, nor can any state face the crisis alone. However, it is important for the state to avoid implementing a particular ideology, as ideology can lead to totalitarianism and restriction of freedoms. In return, Žižek says that if countries move beyond the nation-state stage and move towards a post-nation state by implementing a new form of communism, our liberation, survival and defence will grow and become stronger. Žižek is also interested in the concept of catastrophe and believes that catastrophe helps to rebuild and revive. Although the coronavirus has caused catastrophe, it carries the seeds of revival.